Structural Changes in a Single GaN Nanowire under Applied Voltage Bias; Nano Letters; Vol. 18, iss. 9 - Lazarev S. V. Sergey Vladimirovich; Dzhigaev D. Dmitry; Bi Zh. Zhaoxia; Nowzari A. Ali; Kim A. Young Yong; Rose M. Max (2018, 2018)
Title screen